Integrated SQC and FMEA for Pasted Kraft Cement Bag Defect Mitigation: SQC dan FMEA Terintegrasi untuk Mengurangi Cacat pada Kantong Semen Kraft Berlapis - Aisyah Eka Wulandari; Enny Aryanny (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Product quality is a critical determinant of competitiveness in manufacturing industries, requiring systematic quality control throughout production processes. Specific Background PT X, a pasted kraft cement bag manufacturer, reported a defect rate of 3.2%, exceeding the company tolerance limit of 1.5%, indicating suboptimal quality control performance. Knowledge Gap Previous studies have commonly applied Statistical Quality Control (SQC) and Failure Mode and Effect Analysis (FMEA) separately, with limited integration of both methods for comprehensive defect analysis in cement bag production. Aims This study aims to analyze defect characteristics and develop improvement recommendations using an integrated SQC and FMEA approach. Results The findings reveal four dominant defects: failed bottoming pleats (34.5%), tilted valves (29.4%), poor printing (23.3%), and torn openings (12.8%), with the highest Risk Priority Number (RPN) of 384 attributed to failed bottoming pleats caused by operator inattention during machine adjustment. Novelty This study integrates SQC for defect identification and FMEA for prioritizing root causes and corrective actions in pasted kraft cement bag production. Implications The proposed implementation of a standardized checklist for bottoming machine adjustment parameters before production and after size changes enables consistent machine settings and supports improved quality control practices. Highlights: Failed bottoming pleats constitute the largest proportion of defects at 34.5%. Highest risk priority originates from operator-related machine adjustment errors. Standardized parameter checklist proposed to ensure consistent machine setup. Keywords: Statistical Quality Control, Failure Mode and Effect Analysis, Cement Bag Defects